Effect of Yoga on Adolescents' Attitude towards Violence. (May 2017) - Govindaraja Setty A.G.; Subramanya, Pailoor; Mahadevan, B.
As society progresses with newer technology choices and greater materialistic welfare, we also witness more incidences of aggression and violence among the youth and adolescents. This is partly due to the mental stress that they undergo. There has been a renewed interest to understand the causes of aggression and violence. More importantly, there is an interest to identify methods to manage these. This article is an attempt to showcase the usefulness of yoga in addressing this aspect. The present study was conducted to find out the effect of 4 weeks' yoga practice on 158 (76 girls and 82 boys) normal healthy adolescents' attitude towards violence (ATV) in comparison to practice of physical exercises (PE). The study showed that both yoga and PE groups demonstrated significant reduction in their positive ATV strategies and increased positive use of non-violent strategies. Boys in the yoga group showed significant improvement, whereas the control group showed non-significant improvement. Girls in the yoga also displayed significant progress over the control group. Thus, the study points to the usefulness of introducing yoga to the adolescents in their formative years through a structured curriculum. This is likely to provide numerous benefits both for the individual and the society at large.